Paediatric rational prescribing: a study of paediatric rational prescribing tools and development of a novel tool for the UK - Corrick, Fenella J. (2021)
Background Children are vulnerable to inappropriate prescribing yet rational prescribing criteria, although widely used in adult medicine, are not well-established in paediatric research. Rational prescribing tools, criteria lists of potentially irrational prescribing, are used to study the use of medicines and can be used to detect and quantify inappropriate prescribing. This allows researchers to compare quality of prescribing across different populations, identify factors associated with irrational prescribing, and evaluate the effectiveness of interventions to improve prescribing.